Łowiectwo a obowiązek państwa dbałości o środowisko - Daniłowicz, Witold (Studia Prawnoustrojowe, 2019)
Polish Constitution charges the State with the duty to protect environment. Realizing its obligation the State should, inter alia, regulate hunting in a rational manner. Currently it is the Minister of Environmental Protection who is in charge of that area of activity. The Minister, however, lacks executive organs which could enable him to perform that function. Therefore this role is currently being performed by the Polish Hunting Association and the State Forests. The Minister should oversee their activities in that regard but its powers are very limited, particularly with respect to the Polish Hunting Association. The article puts forward the idea of creating national hunting administration.